Estudio Experimental del Comportamiento de Métricas de QoS y QoE de Streamings de Video Multicast IPTV - Pérez, Santiago Cristóbal (2022)
Digital television is the most important advance in television technology. IPTV describes a mechanism for transporting a stream of video content over a network that uses the IP network protocol. IP Television must be a totally personalized experience that must guarantee Quality of Service (QoS), and QoE (Quality of Experience) within the organization, including the LAN Networks of a Television Channel, or the traditional LAN Networks. In the present research work, the behavior of IPTV traffic was analyzed in an experimental LAN network with controlled traffic. Different codecs were used for contrast, and detailed quantitative results of QoS metrics and, from them, indicative QoE values were established. The findings provide guidance on suitable software and network topology configurations for managing similar networks and provide detailed values for simulation analysts.